Development of a Smart Environment Maturity Model for Green Industry in North Maluku's Mining Villages, Indonesia - Arief, Assaf; Apriyanto, Heri; Muhammad, Miftah; Harisun, Endah (Informatika, Universitas Jenderal Soedirman, 2025)
The smart environment maturity model for sustainable mining village areas in North Maluku Province has become a primary demand for the transformation towards sustainable green smart villages. North Maluku, one of Indonesia's largest mining industry provinces, includes the Halmahera and Obi archipelagos as sources of nickel, iron ore/sand, gold, and silver mines. This study aims to develop a maturity model that integrates Indonsian regulations to support green industry implementation in mining villages. The methodology employs Systematic Literature Review to identify Critical Success Factors (CSFs), validated through expert judgment using 5-point Likert scale assessment. The research results yield eight key dimensions, 25 sub-dimensions, and five maturity levels: underdeveloped, developing, self-reliant, advanced, and smart villages. Expert validation achieved an overall average score of 3.65/5.0, indicating moderate acceptance with improvement areas identified in local culture and technology dimensions. The developed framework provides a foundation for environmental informatics applications and decision support systems in rural development contexts. The model addresses national regulations concerning green industry while providing an adaptive framework for archipelago regions, serving as a reference for policy formulation and village fund allocation based on environmental indicators.